Relationships between competitive wrestling success and neuroendocrine responses - Fry, A. C.; schilling, B. K.; Fleck, S. J.; Kraemer, W. J. (The Journal of Strength and Conditioning Research, 2011)
Previous research on wrestling suggests winning wrestlers will have a greater increase in testosterone (Tes) than losing wrestlers, although the physiological mechanism is unknown. To determine the role of the sympathetic nervous system in this phenomenon, 12 male wrestlers from an National Collegiate Athletic Association Division I program wrestled 5 matches over a 2-day period. Serum samples were collected pre (Pre) and immediately postmatch (Post) for the determination of Tes, cortisol (Cort), Tes/Cort, and epinephrine (Epi). The subjects had a combined record of 34 wins, 31 losses, and 4 ties. Testosterone increased (p < 0.05) for both winners and losers, but the increase was greater for winners (X ± SE; nmol·L-1; winners, pre = 16.4 ± 1.2, post = 23.2 ± 1.5; losers, pre = 14.8 ± 1.0, post = 19.4 ± 1.2). Cortisol and Epi increased similarly for both winners and losers, whereas the Tes/Cort ratio was unaltered at any time. Relative changes in the Epi response (%?) for losers were correlated to %?Tes (r = 0.91), whereas winners did not exhibit similar relationships (r = 0.09). These data suggest that winning wrestlers may use a different regulatory mechanism for their acute Tes responses than losers who appear to depend on sympathetic regulation. Additionally, these data from humans support the biosocial theory of status and the challenge hypothesis developed for competing males in other species.